2020
DOI: 10.1126/scitranslmed.aay9648
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and costs of spinal muscular atrophy drugs

Abstract: Evaluating the benefits, risks, and costs of two drugs to treat spinal muscular atrophy raises questions about the future of rare disease medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 8 publications
0
20
0
1
Order By: Relevance
“…The one-off onasemnogene injection is priced at $2.1 million, the most expensive drug in the world, with nusinersen costing $750,000 in the first year followed by $375,000 annually thereafter, and risdiplam priced at up to $340,000 per year. 8 These costs can clearly lead to major issues for patients and their families as well as healthcare providers (Table 1). Furthermore, although onasemnogene is advertised as a single-injection therapy, it remains unclear whether the treatment will be lifelong or whether additional therapies will be required.…”
Section: Onasemnogene Abeparvovecmentioning
confidence: 99%
See 1 more Smart Citation
“…The one-off onasemnogene injection is priced at $2.1 million, the most expensive drug in the world, with nusinersen costing $750,000 in the first year followed by $375,000 annually thereafter, and risdiplam priced at up to $340,000 per year. 8 These costs can clearly lead to major issues for patients and their families as well as healthcare providers (Table 1). Furthermore, although onasemnogene is advertised as a single-injection therapy, it remains unclear whether the treatment will be lifelong or whether additional therapies will be required.…”
Section: Onasemnogene Abeparvovecmentioning
confidence: 99%
“…Thanks to the development of ground-breaking SMN replacement strategies, there are finally good therapeutic options for families with children diagnosed with SMA, albeit at an extremely high cost. 8 These therapies are completely changing the phenotype of the treated patients, who will no longer follow the natural history of SMA. With a prolonged lifespan and improved neuromuscular function, non-CNS symptoms could become more of a concern in those treated with CNS-targeting therapies.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The present work demonstrated that stimulating MuSK reduces NMJ denervation, accompanied by improved synaptic efficacy and muscle size of these vulnerable muscles in SMA mice. Although MuSK agonist antibody #13 did not increase body weight of SMA mice, its beneficial effects in promoting synapse maintenance and preventing synapse disruption may be used as a complementary therapeutic intervention for SMA patients who may be poor responders to the three currently FDA-approved SMN-enhancing drugs, Spinraza, Zolgensma, and Evrysdi [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 pandemic presented a similar scenario of a new infectious disease for which no treatments or vaccines were available, though most (59%) subjects in its pivotal trial did not respond according to prespecified criteria. 12 Expedited programs are most defensible when applied to drugs that offer large incremental benefits. However, the average share of drugs qualifying for at least 1 expedited program (excluding priority review) was 59% from 2010 to 2019, 13 far exceeding the share of drugs offering major therapeutic gains (Table 1).…”
Section: Disclosuresmentioning
confidence: 99%